Periodontal status of women taking postmenopausal estrogen supplementation - Norderyd, O M; Grossi, S G; Machtei, E E; Zambon, J J; Hausmann, E; Dunford, R G; Genco, R J (Journal of periodontology (1970), 1993)
The association between supplementary estrogen intake and periodontal and gingival status in a total of 228 women 50 to 64 years of age was examined. Clinical parameters including visible supragingival plaque, subgingival calculus, probing pocket depth, clinical attachment level, alveolar bone height measurements, and number of remaining teeth were measured. Gingival status was recorded as gingival bleeding after gentle manipulation. Selected periopathogens, socio-economic, demographic, smoking habits, and health care variables were assessed. Gingival bleeding was significantly lower in the estrogen supplement group (n = 57) compared to the control group (n = 171) (P = 0.009); the estrogen group also exhibited significantly lower visible plaque levels (P = 0.030) and fewer Capnocytophaga-ssp. (P = 0.032). Dental care was more frequent (P < 0.001), and education levels were higher (P = 0.022) in the estrogen group. To investigate whether differences among the above parameters contributed to the difference in gingival bleeding, an age-adjusted analysis of covariance (ANCOVA) was used. The final ANCOVA indicated non-significant relationships for all parameters examined except estrogen intake (P = 0.044). Women taking estrogen exhibited lower gingival bleeding than the control group after correcting for these factors. The results indicate that estrogen supplementation is associated with less gingival bleeding in women aged 50 to 64, as compared to an age-matched control group.